Magnetized sawdust for removal of Cu (II) and Ni (II) from aqueous solutions - Kapur M.; Mondal M.K. (My University, 2025)
An agricultural waste, sawdust was modified into magnetic nanoadsorbent (Fe3O4-SD) and used for single and bicomponent removal of Cu(II) and Ni(II) ions from aqueous solution. Adsorbent particles were characterized through XRD, TEM, FTIR, vibrating sample magnetometer, and Brunauer–Emmett–Teller analysis. The effect of initial metal concentration, contact time, adsorbent dose, pH, and temperature was studied within a suitable range. A contact time of 90 min was needed for equilibrium to be established. Adsorption of Cu(II) and Ni(II) ions onto Fe3O4-SD decreased with increase in temperature showing exothermicity. Process was found to be thermodynamically favorable and spontaneous and physical in nature. Equilibrium data fitted well with Langmuir isotherm model and followed pseudo-second-order kinetics. Adsorption capacity achieved was less when Cu(II) and Ni(II) coexisted in the solution in comparison with when they acted independently, thus supporting antagonistic behavior. Technical feasibility of Fe3O4-SD has been reported in the work and its easy fabrication and reusability make it a promising adsorbent. © 2015 Balaban Desalination Publications. All rights reserved.